Social Implications of COVID-19 in Iran: A Social Work Perspective - Monire Balochi; Amir Moghanibashi-Mansourieh; Reza Dehnavieh; Seyed Hassan Mousavi Chelak; Seyed Mohammad Hossein Javadi; Seyed Reza Javadian; Narges Rostami-Gooran; Khalil Kalavani (Journal of Qualitative Research in Health Sciences)
Background: The widespread and rapid outbreak of COVID-19 shows how a biological and epidemiological issue can affect all aspects of life, including the social domain, leading to short-term and long-term changes in the social and cultural structure of society. Accordingly, the present study aimed to illustrate the social effects of COVID-19 using the futures wheel method.Methods: This qualitative study utilized the futures wheel method. Two groups of experts participated in this study, including experts in the social field at the Institute for Futures Studies in Health and national-level experts in the field of social work. The second version of the futures wheel was implemented in three steps. The identified effects were categorized based on (1) opportunities and threats and (2) time intervals (short-term and long-term). Cases with a support rate of more than 70% were included in the futures wheel as final factors.Results: The findings of this study revealed two main layers of social effects stemming from the COVID-19 outbreak. Home quarantine, social responsibility, social distancing, social security, increased risk for vulnerable social groups, and the use of social networks were the categories identified at the first layer. The second layer included factors such as individualism, social stigma, social exclusion, domestic violence, and an increase in abortions, which threatened Iranian society in a short period.Conclusion: Threats may manifest through social protests, class disparities, and the increase in social disorders in the long run. In the short term, opportunities such as reducing the number of female-headed households and increasing intragroup social capital can also be predicted. Therefore, it is expected that the role of civil society will be strengthened in the long term.